Effect of carnosine, methylprednisolone and their combined application on irisin levels in the plasma and brain of rats with acute spinal cord injury. (August 2015) - Albayrak, Serdal; Atci, İbrahim Burak and Kalayci, Mehmet and Yilmaz, Musa and Kuloglu, Tuncay and Aydin, Suna and Kom, Mustafa and Ayden, Omer and Aydin, Suleyman
Summary: Spinal cord injury (SCI) might occur to anybody at any time and any age. In its treatment, methylprednisolone (MP) is a first choice worldwide, but there is still no significant breakthrough in truly beneficial treatment due to SCI's complex pathophysiology. We investigated the effect of carnosine, methylprednisolone (MP) and its combination on irisin levels in the plasma, brain and medulla spinalis tissues in SCI using a rat model. The rats were divided into 6 groups: I (Control, saline); II (sham animals with laminectomy without cross-clamping); III (SCI); IV (SCI treated with 150 mg/kg carnosine); V (SCI treated with 30 mg/kg methylprednisolone); and VI (SCI treated with a combination of carnosine and MP). The animals were given traumatic SCI after laminectomy, using 70-g closing force aneurysm clips (Yasargil FE 721). Irisin concentration was measured by ELISA. The distribution of irisin in brain and spinal cord tissues was examined by immunochemistry. Irisin was mainly expressed in the astrocytes and microglia of brain tissues, and multipolar neurones of the anterior horn of spinal cord tissue in rats of all groups, indicating that irisin is physiologically indispensable. MP and carnosine and the combination of the two, significantly increased irisin in plasma and were accompanied by a significant rise in irisin immunoreactivity of brain and spinal cord tissues of the injured rats compared with control and sham. This finding raises the possibility that methylprednisolone and carnosine regulate the brain and spinal cord tissues in SCI by inducing irisin expression, and may therefore offer a better neurological prognosis. Highlights: Methylprednisolone (MP) and carnosine treatment in SCI increases irisin expression. Irisin measurement might be useful relative to the efficacy of MP and carnosine. Irisin is expressed in the multipolar neurones of anterior horn of spinal cord tissue of rats. Irisin has a higher express level in spinal cord than in brain tissues. Carnosine treatment might be the alternative to MP treatment in spinal cord injury.